Development and Evaluation of Cow Dung Composting Equipment with Ventilation and Heating - Kailin Ren; Lide Su; Yong Zhang; Xiang He; Hao Wu (Applied Sciences, 2023)
Traditional cow manure composting equipment often lacks ventilation, heating, and real-time monitoring and adjustment capabilities, hindering manure maturation and proper utilization of compost, moisture reduction, and optimal environmental conditions for microbial activity. To address these limitations, we optimized and redesigned the structure and control elements of conventional composting equipment. In doing so, we developed a novel cow manure composting apparatus based on the target composting quantity method. The new design features a refined ventilation and heating structure, as well as an enhanced control system using PLC and MCGS. This equipment provides improved composting effects while offering real-time monitoring of composting data, effectively promoting the composting process. Further evaluation of the modified equipment was conducted using fermented cow dung, demonstrating its feasibility. The experiment yielded positive results, indicating that the composted cow manure satisfied all necessary standards across all evaluation parameters. These parameters included the moisture content of the compost, the duration of high temperature, the pH, and the seed germination index. The seed germination rate reaches 85%, and the water content of manure is 9.3%, which is much higher than the industry standard.